2012
DOI: 10.1002/adma.201201879
|View full text |Cite
|
Sign up to set email alerts
|

Design Scheme of New Tetragonal Heusler Compounds for Spin‐Transfer Torque Applications and its Experimental Realization

Abstract: Band Jahn–Teller type structural instabilities of cubic Mn2YZ Heusler compounds causing tetragonal distortions can be predicted by ab initio band‐structure calculations. This allows for identification of new Heusler materials with tunable magnetic and structural properties that can satisfy the demands for spintronic applications, such as in spin‐transfer torque‐based devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 246 publications
(153 citation statements)
references
References 31 publications
3
148
1
1
Order By: Relevance
“…Examples of known tetragonally distorted Heuslers 57 However, films of the Rh 2 -compounds show in-plane magnetization, 58 in accordance with theory. 54 At high temperature and in a high magnetic field, these materials are cubic (austenite phase). 59 Jahn Teller and van Hove can play a role in the same system since a degenerate state goes along with a high density of states as, for example, in Mn 3 Ga.…”
Section: Apl Mater 3 041518 (2015)mentioning
confidence: 99%
“…Examples of known tetragonally distorted Heuslers 57 However, films of the Rh 2 -compounds show in-plane magnetization, 58 in accordance with theory. 54 At high temperature and in a high magnetic field, these materials are cubic (austenite phase). 59 Jahn Teller and van Hove can play a role in the same system since a degenerate state goes along with a high density of states as, for example, in Mn 3 Ga.…”
Section: Apl Mater 3 041518 (2015)mentioning
confidence: 99%
“…Recently, it was shown that partial substitution of Mn by Co in Mn 3−x Co x Ga changes the crystal structure from tetragonal to cubic when the Co content x is increased, leading to a reduction of the saturation magnetisation [10,11,12]. Kubota et al [13] investigated the composition dependence of the structural, magnetic, and transport properties of epitaxially grown Mn-Co-Ga films.…”
Section: Introductionmentioning
confidence: 99%
“…10 On the other hand, the magnetizations of both Pt-containing samples show clear magnetic transitions near 200 K and 370 K. The magnetic transition at 370 K is consistent with the predicted Curie temperature (T c ¼ 374 K) of Mn 2 PtSn. 7 Since our samples contain a small amount of Mn 2 Sn and the Curie temperature of ferromagnetic Mn 2 Sn is close to 200 K, the transition near 200 K can be explained by the presence of Mn 2 Sn.…”
Section: Resultsmentioning
confidence: 99%
“…Mn 2 PtSn is of special interest because of the predicted high magnetocrystalline anisotropy ($50 Mergs/cm 3 ) and high spin polarization (P ¼ 91%) at the Fermi level. 7,8 Mn 3 Sn has been predicted to exist in both hexagonal D0 19 and tetragonal D0 22 crystal structures; however, only the hexagonal phase (a ¼ 5.665 Å , c ¼ 4.531 Å ) has been synthesized in experiment. 9 At room temperature, the hexagonal Mn 3 Sn exhibits a triangular antiferromagnetic order, where the Mn-sublattice magnetizations lie in the plane perpendicular to the hexagonal basal plane resulting in zero net magnetization.…”
Section: Introductionmentioning
confidence: 99%